∫ 0 ∞ tanh ( π x ) ( x 1 − 1 6 1 + x 2 x ) d x can be written in the form b π a − ln ( c ) where a and b are positive integers.
What is the value of a + b + c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that the above integral can be expressed as n ≥ 0 ∑ ( 2 n + 1 ) ( 4 n + 3 ) 2 = ψ 0 ( 4 3 ) − ψ 0 ( 2 1 ) = 2 π − ln 2 Further this integral can be generalized and it has close relation with this problem.
Problem Loading...
Note Loading...
Set Loading...
First note that j = 1 ∑ J ( 2 j − 1 ) ( 4 j − 1 ) ( 4 j − 3 ) 1 = j = 1 ∑ J ( 4 j − 1 1 + 4 j − 3 1 − 2 j − 1 1 ) = j = 1 ∑ 2 J 2 j − 1 1 − j = 1 ∑ J 2 j − 1 1 = j = 1 ∑ 4 J j 1 − j = 1 ∑ 2 J 2 j 1 − j = 1 ∑ 2 J j 1 + j = 1 ∑ J 2 j 1 = ( S 4 J + ln ( 4 J ) ) − 2 3 ( S 2 J + ln ( 2 J ) ) + 2 1 ( S J + ln J ) = S 4 J − 2 3 S 2 J + 2 1 S J + 2 1 ln 2 where S J = j = 1 ∑ J j 1 − ln J is well-known to converge to the Euler-Mascheroni constant γ . Thus we deduce that j = 1 ∑ ∞ ( 2 j − 1 ) ( 4 j − 1 ) ( 4 j − 3 ) 1 = 2 1 ln 2 Consider the desired integral X = ∫ 0 ∞ tanh ( π x ) ( x 1 − 1 6 1 + x 2 x ) d x = ∫ 0 ∞ x ( 1 + 1 6 x 2 ) tanh ( π x ) d x = 2 1 ∫ − ∞ ∞ x ( 1 + 1 6 x 2 ) tanh ( π x ) d x The function z ( 1 + 1 6 z 2 ) tanh ( π z ) is meromorphic, with a removable singularity at z = 0 , and its simple poles in the upper half plane are at z = ( j − 2 1 ) i for all j ∈ N .
If C N is the square with vertices N + N i , − N + N i , − N − N i , N − N i , it is standard theory that ∣ tanh ( π z ) ∣ ≤ coth π for all z ∈ C N and all N ∈ N . Thus, if R N is the positively oriented rectangle with vertices N , N + N i , − N + N i , − N , then N → ∞ lim ∫ R N z ( 1 + 1 6 z 2 ) tanh ( π z ) d z = 2 X On the other hand, residue calculus tells us that ∫ R N z ( 1 + 1 6 z 2 ) tanh ( π z ) d z = 2 π i { R e s z = 4 1 i + j = 1 ∑ N R e s z = ( j − 2 1 ) i } z ( 1 + 1 6 z 2 ) tanh ( π z ) = 2 π i { − 2 1 i + j = 1 ∑ N π ( j − 2 1 ) i [ 1 − 4 ( 2 j − 1 ) 2 ] 1 } = π − j = 1 ∑ N ( 2 j − 1 ) ( 4 j − 1 ) ( 4 j − 3 ) 4 Letting N → ∞ we deduce that X = 2 1 π − ln 2 making the answer 1 + 2 + 2 = 5 .